The geographical distribution of the production of grain crops and their relationship to water resources in Anbar Governorate - Assist. Prof. Hazem Jawad Kazem (Journal of College of Education, 2024)
The reality of grain crops represented (wheat, barley, yellow corn) in the districts and districts of Anbar Governorate for the year 2022 was examined, where the hypothesis is based that there is a decrease in the production of one dunum per unit area and production from agricultural lands as a result of the presence of problems, including those related to the nature of agricultural land, and others related to climatic conditions and technical factors. The research relied on the analytical descriptive approach based on scientific research, documents and official reports in collecting and organizing information and drawing conclusions, then addressing the reality of grain crops in the province and working to increase production. The possibility of expanding and increasing the agricultural lands was reached through the reclamation of the desert, saline and gypsum lands, and the adoption of modern methods of agriculture and the provision of water and the rationalization of its use, all of which lead to an increase in production.
Keywords: grain crops, water resources, Anbar